Houses in Bucharest and their narrative function in "Forbidden" Forest by Mircea Eliade - Sava, Monica (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2013)
The narrative world of the Forbidden Forest points out that Mircea Eliade, aware of the inconsistency of the frontiers between art and reality, history and fiction, biography and imagination, doesn’t limit himself to create in his novel a mere frame of epoch. Despite its obvious documentary character, the environment of Bucharest appears as a space where historic events prove to be “trials of labyrinth”. The space of inter-war Bucharest acquires mythological values, turns into a codified world where the sacred can manifest itself disguised under the most trivial aspects, into a parallel universe that allows the quest for a possible way out of the History.
Keywords: urban space; Bucharest; house; Mircea Eliade